DRT111/SFPS Splicing Factor Controls Abscisic Acid Sensitivity during Seed Development and Germination . Issue 2 (2nd March 2020) - Punzo, Paola; Ruggiero, Alessandra; Possenti, Marco; Perrella, Giorgio; Nurcato, Roberta; Costa, Antonello; Morelli, Giorgio; Grillo, Stefania; Batelli, Giorgia
Abstract : Arabidopsis DNA-DAMAGE REPAIR/TOLERATION PROTEIN111/SPLICING FACTOR FOR PHYTOCHROME SIGNALING regulates pre-mRNA splicing in seeds, affecting ABA-mediated responses. Abstract: RNA splicing is a fundamental mechanism contributing to the definition of the cellular protein population in any given environmental condition. DNA-DAMAGE REPAIR/TOLERATION PROTEIN111 (DRT111)/SPLICING FACTOR FOR PHYTOCHROME SIGNALING is a splicing factor previously shown to interact with phytochrome B and characterized for its role in splicing of pre-mRNAs involved in photomorphogenesis. Here, we show that DRT111 interacts with Arabidopsis ( Arabidopsis thaliana ) Splicing Factor1, involved in 3′ splicing site recognition. Double- and triple-mutant analysis shows that DRT111 controls splicing of ABI3 and acts upstream of the splicing factor SUPPRESSOR OF ABI3–ABI5. DRT111 is highly expressed in seeds and stomata of Arabidopsis and is induced by long-term treatments of polyethylene glycol and abscisic acid (ABA). DRT111 knock-out mutants are defective in ABA-induced stomatal closure and are hypersensitive to ABA during seed germination. Conversely, DRT111 overexpressing plants show ABA-hyposensitive seed germination. RNA-sequencing experiments show that in dry seeds, DRT111 controls expression and splicing of genes involved in osmotic-stress and ABA responses, light signaling, and mRNA splicing, including targets of ABSCISIC ACID INSENSITIVE3 (ABI3) and PHYTOCHROME INTERACTING FACTORs (PIFs). Consistently, expression of the germination inhibitor SOMNUS, induced by ABI3 and PIF1, is upregulated in imbibed seeds of drt111 - 2 mutants. Together, these results indicate that DRT111 controls sensitivity to ABA during seed development, germination, and stomatal movements, and integrates ABA- and light-regulated pathways to control seed germination.